Preface to Rewriting Logic and Its Applications (revised selected papers from WRLA 2020) - Escobar, Santiago; Martí-Oliet, Narciso (Journal of logical and algebraic methods in programming, 2025)
This special issue collects revised extended versions of selected papers presented at the 13th International Workshop on Rewriting Logic and Its Applications (WRLA 2020) held as an online event from October 20 to 22, 2020.